2007
DOI: 10.1158/0008-5472.can-06-4024
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue–Derived Human Mesenchymal Stem Cells Mediated Prodrug Cancer Gene Therapy

Abstract: Human adipose tissue-derived mesenchymal stem cells (AT-MSC) are considered to be a promising source of autologous stem cells in personalized cell-based therapies. Tumor tracking properties of MSC provide an attractive opportunity for targeted transgene delivery into the sites of tumor formation. In the present study, we addressed whether the suicide gene introduction into human AT-MSC could produce a tumor-specific prodrug converting cellular vehicle for targeted chemotherapy. We prepared yeast fusion cytosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
403
3
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(442 citation statements)
references
References 33 publications
9
403
3
8
Order By: Relevance
“…However, others have shown that MSC with ectopic gene expression can inhibit growth of pulmonary and subcutaneous xenografts after systemic transplantation. 26,27 In accordance with preliminary data in our model, we hypothesize that under optimized conditions, tumor integration of TRAIL-MSC may be enhanced, resulting in a potent anti-tumor activity.…”
Section: Discussionsupporting
confidence: 87%
“…However, others have shown that MSC with ectopic gene expression can inhibit growth of pulmonary and subcutaneous xenografts after systemic transplantation. 26,27 In accordance with preliminary data in our model, we hypothesize that under optimized conditions, tumor integration of TRAIL-MSC may be enhanced, resulting in a potent anti-tumor activity.…”
Section: Discussionsupporting
confidence: 87%
“…31 Because of such properties, MSCs are considered potentially efficient vehicles for cancer therapeutic genes. 32 The tumor stroma plays a supporting role in the propagation or dissemination of tumors by producing protumorigenic cytokines. 33 A prior study demonstrated that with the exposure to tumor cell-conditioned medium, migration of MSCs was promoted with an increase in stromal cell-derived factor-1 protein production.…”
Section: Discussionmentioning
confidence: 99%
“…L'administration de CSM que l'on force à exprimer la thymidine kinase permet de réduire fortement la croissance de tumeurs de la prostate [23]. Un autre système de prodrogue, cette fois fondé sur l'utilisation de la cytosine désaminase (CD), a été utilisé pour traiter des souris qui présentaient une tumeur du côlon [24]. Dans ces études, les auteurs ont fait exprimer à des CSM la CD, ont injecté ces cellules aux animaux qu'ils ont ensuite traités avec du 5'fluorouracile (5-FU).…”
Section: Les Csm : Véhicules Pour Une Thérapie Cellulaire Antitumoraleunclassified